Incidental vocabulary learning in second language acquisition: a literature review (2015)
This literature review aims to analyze previous studies that address the incidental learning of vocabulary in second language acquisition. The articles included in this literature review look into the understanding of vocabulary learning through incidental means, the relationship of reading and incidental vocabulary learning, and the strategies and tasks that promote the incidental learning of vocabulary. The findings show that L2 learners develop much of their vocabulary by incidental means through exposure to words in informative contexts. Moreover, this exposure is promoted by reading, and enhanced through multimodal glosses. Further research may focus on listening for higher lexical retention rates, the circumstances that allow incidental learning of multi-word phrases and collocations, and the use of technology-based methods for incidental vocabulary acquisition.Esta revisión de literatura analiza estudios previos sobre el aprendizaje incidental de vocabulario en la adquisición de una segunda lengua. Estos artículos estudian la naturaleza del aprendizaje incidental de vocabulario, la lectura y la adquisición incidental de vocabulario y las estrategias que la promueven. Encontramos que los estudiantes de una segunda lengua desarrollan la mayoría de su vocabulario incidentalmente por medio de la ocurrencia léxica en contextos altamente informativos. Asimismo, la lectura y las anotaciones multimodales incentivan y complementan la ocurrencia de este vocabulario. Investigaciones futuras podrían enfocarse en la escucha como medio de mayor retención léxica, en las circunstancias que permiten el aprendizaje incidental de colocaciones, y en el uso de la tecnología para la adquisición incidental de vocabulario.